The Canadian quandary : economic problems and policies - Johnson, Harry G. (Harry Gordon), 1923-1977 (Carleton library series, 2005)
The Canadian Quandary is a collection of unbuttoned pieces written in Johnson's witty and acerbic style between 1958 and 1963. Dealing with Canadian policy on trade and foreign policy, the volume includes Johnson's classic dismemberment of the Canadian nationalist movement. Though Trudeau's Foreign Investment Review Agency and National Energy Policy have long since been dismantled, economic nationalism persists and it is a testament to both the lucidity of Johnson's mind and the vigour and clarity of his writing that many of his opinions on this debate are still fresh, interesting, and relevant.